2019
DOI: 10.21032/jhis.2019.44.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Correlation between Knowledge-Barriers/Facilitators for Pressure Ulcer Prevention Nursing Variables and Attitude-Performance Variables

Abstract: Objectives: Knowledge, barriers/facilitators for pressure ulcer prevention nursing are correlated with attitude and performance of staff nurses. It can be helpful to utilize barriers and facilitators for enhancing the attitude and performance of nurses, there is a gap in the empirical study. The aim of this study was to investigate the relationship between knowledge-barriers/facilitators for Pressure Ulcer (PU) prevention variable set and attitude-nursing performance variable set. Methods: This study employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 21 publications
3
9
1
3
Order By: Relevance
“…This is in line with the findings that attitude affects intention to perform skin PU prevention [ 16 ] and actual performance [ 19 ]. Previous research has also shown a positive relationship between facilitators and performance, which corroborates the current study’s results [ 21 ]. Attitude was defined as behavioral intent and the amount of regard for or against an object, which is affected by knowledge [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This is in line with the findings that attitude affects intention to perform skin PU prevention [ 16 ] and actual performance [ 19 ]. Previous research has also shown a positive relationship between facilitators and performance, which corroborates the current study’s results [ 21 ]. Attitude was defined as behavioral intent and the amount of regard for or against an object, which is affected by knowledge [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…The mean score of attitudes toward oral mucosa PU prevention was similar to that of skin PU prevention in previous studies [ 19 , 21 ]. According to recent studies, oral mucosa PU is a common MDRPU [ 4 ], it improves in 2–3 days, and relapses frequently compared to skin PUs [ 5 ].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations